Not that kind of ever after - Adams, Luci (St. Martin's Griffin, 2023)
"Bella Marble's life isn't what she imagined. Instead of an author, she's receptionist at a small press. Instead of happily married, she's single, and her lovey-dovey parents are divorcing. And to top it off, her best friend of twenty-nine years, Ellie Mathews, is moving out and marrying the heinously boring Mark. (He's not worthy of her. No one could be). Bella feels rudderless, only slightly soothed by time spent with Ellie's (not hot) brother, (he's not hot) Marty (okay, he's hot. But he's also the aggravating brother she never had-right)? When Marty recommends Bella stop looking for "the one" and just have fun, Bella finds a new, empowered side of herself. But when she posts a fairy-tale retelling of a disastrous one night stand on a storytelling app, all of a sudden, Bella has become @B.Enchanted. And she's gone viral. Now, Bella's in a fight with Ellie, her new roommates are so, deeply, weird, and the pressure is mounting to find new fairy tales to write about-but she's got to live them first. A bold and brilliantly funny novel, Not That Kind of Ever After celebrates empowered women, the complexities of dating, and the nuances of lifelong love in all its forms. Because sometimes you need a lost shoe, a drunken escapade with some Smurfs, and one very potent Gingerbread House, to show you how to find your way back to those you love"--